Síndrome de Asperger: práticas inclusivas no processo de alfabetização/letramento - Bruno, Daniele Lúcia de Freitas (2016)
The objective of the research was to investigate the influence of the conditions of access and permanence of people with autism spectrum disorder in the Initial Years of the College of Application of the Higher Education Institute of Rio de Janeiro (CAp - ISERJ). The process of inclusion of these in the different contexts of school life, focusing on the study of the acquisition process of reading and writing of a student diagnosed with Asperger Syndrome. This study is relevant in several aspects, since it will signal how the literacy / literacy process takes place from the perspective of inclusion, interaction and school socialization described by teachers and family members. The bibliographical research was based predominantly on the theoretical basis of authors such as Freire (1987, 1996, 2000), Garcia (2004), Beyer (2010), Coll (2004), Cardoso (2008) and Ferrari (2007). The methodology adopted in the research was the case study, using the following instruments for data collection: interviews directed to teachers and families and descriptive analysis of student didactic material. Through the interviews, the teachers' and teachers' considerations regarding the teaching-learning process were analyzed, aiming to analyze the subjects' perceptions (teachers and family members) regarding the performance, practices and results obtained by the student, confronted with the observation record Of the behavior of the same in different moments of learning, through their productions. It is hoped that the research can contribute to (re) think the process of literacy and literacy of children with autism spectrum disorder, indicating ways to school inclusion.